Effect of reaction parameters on the lipase-catalyzed kinetic resolution of (RS)-metoprolol - Mariani, Rajin; Asiah, Zulkifli; Sariah, Abang; S. M., Anissuzzaman; A. H., Kamaruddin (ASEAN Chemical Engineers, 2020)
Racemic metoprolol is a selective Ã1-blocker, which is used in cardiovascular disease treatment. It has been found that (S)-metoprolol has a higher affinity to bind the Ã-adrenergic receptor compared to (R)-metoprolol. Moreover, the regulatory authoritiesâ high market demand and guidelines have increased the preference for single enantiomer drugs. In this work, the lipase-catalyzed kinetic resolution of racemic metoprolol was performed to obtain the desired enantiomer. The type of lipase, acyl donor, and solvent were screened out. This was achieved by Candida antarctica B lipase-catalyzed transesterification of racemic metoprolol in hexane and vinyl acetate as the solvent and an acyl donor, which gave maximum conversion of (S)-metoprolol (XS) of 52, enantiomeric excess of substrate, (ees) of 92 and product (eeP) of 90 with enantiomeric ratio (E) of 62. This method can be considered as green chemistry, which can be applied to produce other enantiopure beta-blockers. Â© 2020, Gadjah Mada University. All rights reserved.